CONSUMER SATISFACTION BEHAVIOR WHOM PURCHASE CHINESE SMARTPHONE IN SOLORAYA - Putra, Febrianur Ibnu Fitroh Sukono; Budiantoro, Risanda Alirastra; Luxfiati, Bilkis Aulia; Widawati, Mega Wahyu (Jurnal Aplikasi Manajemen, 2020)
Customer satisfaction behavior that buys Chinese smartphone products is the purpose of this research. This research population is all customers who bought Chinese smartphones in seven cities included Surakarta, Boyolali, Sukoharjo, Wonogiri, Sragen, Klaten, and Karanganyar in Central Java. The sampling technique used purposive sampling with a total of 400 respondents who bought Chinese smartphones in the official store and black market. A personal questionnaire obtained by a field study is a data collection research method. Multiple linear regression and comparison tests used as an analysis tool in this research. The findings in this research resulted that the three independent variables such as price perception, product quality, and marketplace have a positive and significant effect on customer satisfaction. In this study, it was also found that there were differences in consumer satisfaction who bought the Chinese smartphones in official stores and the black market.